The Effect of Board Race Game Towards Students’ Vocabulary Mastery At The Eighth Grade Students of MTs Nurul Hidayah Malingping Lebak Banten in Academic Year 2023/2024 - Risa, Risa; Riandi, Riandi; Rohimajaya, Nur Azmi (Universitas Mathla'ul Anwar Banten, 2023)
This This study aimed to investigate The Effect of Board Race Game Towards Students’ Vocabulary Mastery at the Eighth Grade Students of MTs Nurul Hidayah Malingping Lebak Banten in Academic Year 2023/2024. The research uses quantitative approach and quasi-experimental design. This study used two classes, they are control class and the experimental class. The technique used for collecting sampling is purpose sampling; the researcher uses class VIII A (20 students) as the control class and class VIII B (20 students) as the experimental class. The experimental class was given treatment board race game, while the control group was given treatment guessing game. In data collection technique, the researcher performs pre-test and post-test. The control group's pre-test score was 1044, while the experimental group's pre-test score was 1184. The control group's post-test score was 1250, while the experimental group's post-test score was 1387. During the process to analyze the data, the researcher used the SPSS 25 statistical calculation method and used the post-test results of both the control and experimental classes to analyze and test the hypothesis. The researcher finds the results Two-sided significance = 0.000 < α 0.05. Therefore, the researcher concludes that board race use has a significant impact on students' vocabulary mastery in MTs Nurul Hidayah Malingping Lebak Banten.